2019
DOI: 10.1242/dev.175257
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal proteases and tissue fluidity remodel the extracellular matrix during airway epithelial branching in the embryonic avian lung

Abstract: Reciprocal epithelial-mesenchymal signaling is essential for morphogenesis, including branching of the lung. In the mouse, mesenchymal cells differentiate into airway smooth muscle that wraps around epithelial branches, but this contractile tissue is absent from the early avian lung. Here, we have found that branching morphogenesis in the embryonic chicken lung requires extracellular matrix (ECM) remodeling driven by reciprocal interactions between the epithelium and mesenchyme. Before branching, the basement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 82 publications
(96 reference statements)
1
46
0
Order By: Relevance
“…This discovery was rooted firmly in airway biology. Since that time, the concept of cell jamming has diffused widely into the study of other collective cellular systems, and growing evidence from us and others now suggests that the capacity to jam and unjam may be an innate property of many epithelia both in normal development (Atia et al, 2018;Mongera et al, 2018;Spurlin et al, 2019) and in disease (Sadati et al, 2013;Haeger et al, 2014;Park et al, 2015;Bi et al, 2016;Gamboa Castro et al, 2016;Oswald et al, 2017;Atia et al, 2018;Mongera et al, 2018;Palamidessi et al, 2018Palamidessi et al, , 2019Fujii et al, 2019;Spurlin et al, 2019), including asthma (Angelini et al, 2011;Nnetu et al, 2012;Garcia et al, 2015;Park et al, 2015Park et al, , 2016Malinverno et al, 2017;Atia et al, 2018), and cancer (Haeger et al, 2014;Oswald et al, 2017;Palamidessi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discovery was rooted firmly in airway biology. Since that time, the concept of cell jamming has diffused widely into the study of other collective cellular systems, and growing evidence from us and others now suggests that the capacity to jam and unjam may be an innate property of many epithelia both in normal development (Atia et al, 2018;Mongera et al, 2018;Spurlin et al, 2019) and in disease (Sadati et al, 2013;Haeger et al, 2014;Park et al, 2015;Bi et al, 2016;Gamboa Castro et al, 2016;Oswald et al, 2017;Atia et al, 2018;Mongera et al, 2018;Palamidessi et al, 2018Palamidessi et al, , 2019Fujii et al, 2019;Spurlin et al, 2019), including asthma (Angelini et al, 2011;Nnetu et al, 2012;Garcia et al, 2015;Park et al, 2015Park et al, , 2016Malinverno et al, 2017;Atia et al, 2018), and cancer (Haeger et al, 2014;Oswald et al, 2017;Palamidessi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since this discovery of these dynamic and structural hallmarks of epithelial UJT (Park et al, 2015;Atia et al, 2018), work from our team and others now suggests that the UJT seems to be a normal and perhaps essential part of epithelial biology but, nonetheless, can become hijacked in disease. For example, in the healthy embryo in vivo the UJT is triggered during ventral furrow formation during gastrulation in Drosophila (Atia et al, 2018), during elongation of the vertebrate body axis in the embryonic zebrafish (Mongera et al, 2018), and during airway epithelial branching in the embryonic avian lung (Spurlin et al, 2019). The UJT is therefore observed across vastly diverse biological contexts, in normal development and disease, both in vitro and in vivo, but its mechanisms and stimuli provoking the UJT are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Forces and relative movement between cells and ECM are particularly important in sculpting tissues during development. [ 11–14 ] Researchers have therefore begun to engineer dynamic interactions between cells and ECM in order to guide multi‐cellular structure formation. [ 15–24 ] For example, Davidson et al found that networks of contractile endothelial cells with different morphologies could be generated by varying the extent to which cells were able to physically reorganize surrounding ECM fibers.…”
Section: Figurementioning
confidence: 99%
“…The epithelial layer is ordinarily non-migratory, jammed and quiescent but all the time retains the capacity to unjam and transition to a migratory phase in response to the demand for tissue development, growth, remodeling or wound repair 19,29,48 . It has been suggested that these salutary unjamming behaviors can sometimes become hijacked in disease, however, and thereby initiate unwelcomed cellular migration and tissue remodeling as in the cases of tumor invasion or asthmatic remodeling of the airway wall 24,[49][50][51] .…”
Section: Discussionmentioning
confidence: 99%